An Analysis of Cryptocurrency: Islamic Law Perspective - Abubakar Ibrahim Adamu; Ardo, Hamidu; Bomai, Najaatu Mohammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is to analyze the cryptocurrency from Islamic Perspective. Cryptocurrency is a new phenomenon to Islamic Law. It is a digital currency that is neither issued by a central bank nor a public authority, but accepted as a medium of exchange by some individuals and entities and can be transferred, stored or traded electronically. Its legal nature remains unclear some are considering it as only medium of exchange while others as commodity, couple with some of its peculiar features such as anonymity of transacting parties, lack of control and supervision by a central authority, intangibility and speculation. The paper begins with brief introduction on the Islamic law principles governing commercial transactions. The paper continues with the explanation of the concept, nature and scope of cryptocurrency from Islamic Perspective. Analytical research methodology is used to analyze the work. At the end it is observed that contemporary Muslims scholars differ as to the position of cryptocurrency in Sharia. Some look at it as halal (permissible) in principle, while others look at it as haram (prohibited). However, the research recommends that a further research need to be conducted as to the actual legal status of cryptocurrency and its impact in both social and economic life of Muslims, this will assist in making a final decision on it.